Reclaiming the Night-Time Economy - Fileborn, Bianca (Palgrave Macmillan UK, 2016)
Keywords: Alcohol; Assemblage; Camille; Community; Crime prevention; Criminology; Culture; Drugs; Environmental design; Gender; LGBTIQ; Licensed venues; Safety; Sexual consent; Sexual ethics; Sexual offending; Sexual violence; Sexuality; Space; Young people

Doing gender, doing safety? Young adults’ production of safety on a night out - Fileborn, Bianca (Gender, Place & Culture, 2016)
This article explores the ways in which young adults produce a sense of safety in pubs and clubs. Despite considerable anxiety around issues pertaining to safety and violence in the night-time economy, there is little consideration of how young adults themselves feel about their safety on a night out, or how they achieve a sense of safety in a seemingly ‘risky’ social space. Drawing on mixed-methods research conducted in Melbourne, Australia, in this article I consider the strategies that young adults used to feel safe on a night out. I argue that feeling ‘safe’ is something that is actively produced through the use of these strategies, as well as providing an avenue for ‘doing’ gender.
Keywords: Camille; Safety; Seguridad; economía nocturna; feminidad; femininity; gender performance; licensed venues; locales autorizados; masculinidad; masculinity; night-time economy; performance de género; 夜间经济; 女性气质; 安全; 性别展演; 拥有许可证之营业场所; 男性气概